An innovative method for accelerating vaccine formulation development and manufacturing process: Using prefabricated vaccine base (standardized mixtures of vaccine excipients) - Berhanu, Mulugeta (My University, 2021)
Vaccine base can be defined as a standardized mixtures of vaccine excipients such as adjuvants emulsifier, preservatives, stabilizer, surfactant, buffers and etc. Vaccine bases are substances to which antigen (s) is/are added to form the final product (vaccine) which can provide protection against infectious disease. Prefabricated vaccine base can be used to develop vaccines in an easy and fast way. With vaccine base we do not need to formulate vaccines from scratch. Just we incorporate antigen of interest in vaccine base and vaccine is completed. Thus, premade vaccine base can be used to accelerate vaccine formulation development during global pandemics and epidemics. Using prefabricated vaccine base for vaccine development against various infectious diseases is an innovative method for accelerating deployment of existing and novel vaccines. Prefabrication of vaccine base is a new preparedness strategy for the future pandemics.
Keywords: Accelerating vaccine formulation development; Antigen of interest; Prefabricated vaccine base; Vaccine; Vaccine Excipients